PERLINDUNGAN HUKUM BAGI PENUMPANG PADA ANGKUTAN UMUM DITINJAU DARI KELAIKAN JALAN KENDARAAN BERMOTOR - Sunardi, Sunardi; Sidarta, Dudi Djaja; Ayungtyas, Fitri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The transportation sector plays a very vital role in community life. Passengers, as consumers or users of public transportation services, must receive good service from both the government and transportation service providers. In addition, protection of the rights of the community as passengers must also be clear. Article 48 of Law Number 22 of 2009 concerning Traffic and Road Transportation stipulates that every motor vehicle operating on the road must meet technical requirements and be roadworthy. Every vehicle operating on the road must undergo motor vehicle testing. A motor vehicle can be declared roadworthy if it has passed the motor vehicle test and obtained approval of the test results on the proof of periodic test completion. Motor vehicle testing can be said to be one of the efforts to provide legal protection for passengers. What is the form of legal protection for passengers in public transport that do not meet roadworthiness for motor vehicles? There needs to be an identification of the forms or efforts of legal protection in order to ensure the fulfillment of passenger rights in public transportation